(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2020)
The article actualizes the expediency of accounting support of the financial planning process in order to minimize costs. Accounting procedures are identified at each stage of financial planning. It was systemized the accounting registers, which are used to group information about the assets and liabilities of the enterprise during the reporting period. Such information is used in analytical work, planning, budgeting and business process management. In each group of registers was identified information that can be used in financial planning. The forecast indicators of the plan of incomes and expenses from operational, financial and investment activity of the enterprise were systematized. Emphasis is placed on the expediency of forming a plan of cash receipts and expenditures in order to monitor the provision of solvency at all stages of the planning period. It was carried out the classification of forecast indicators of the plan of receipts and expenditures of cash in the context of indicators of operating, investment and financial activities. Moreover it was performed the analysis of the structure of the balance of monetary resources as the final document of the current financial plan.